Incidente de desconsideração da personalidade jurídica - Santos, Elaine Pacheco dos (2017)
This is the work of completing a course (monograph) to obtain the title of specialist in civil procedural law. The present work sought to synthesize the lines of reasoning used to deal with the novel incident of disregarding the legal personality and its unfolding in the procedural and material legal sphere. It analyzed the main characteristics of the implementation process, addressing its definition and principles. After addressing the issue of primary and secondary patrimonial responsibility, highlighting the differences and importance in relation to the theme chosen. He also highlighted the benefit of the order of the partners. Regarding the disregard of personality, he discussed the historical evolution of the concept of legal personality, its theories, authorizing requirements, effects (including before economic groups), practical application. Regarding legitimacy, it analyzed whether it would be possible to establish an official document and the new and interesting hypotheses legitimized that only arose from the positiveness of the procedural rules of the incident. It also considered the legal nature of the decision granting disregard and appropriate recourse. It brought reflections about the concept of fraud to execution and fraud against creditors and the importance of this institute in combating them. Synthesized the incident of inconsideration in reverse mode. The present work will have as base of research the most recent specialized doctrine, besides the jurisprudence totally focused on the subject